Exploring sustainable development : geographical perspectives - Purvis, Martin; Grainger, Alan (Earthscan, 2004)
"This book explores different interpretations of sustainable development in both theory and practice, in developed and developing countries, and in rural and urban areas. It pays particular attention to the local, national and international politics of implementation, the future of climate and energy, the role of business, and different conceptions of agricultural sustainability." "This wide-ranging text is ideal for undergraduates and postgraduates in geography, environmental science, development studies, and related social and political sciences."--Jacket